A Story Written with Water - Ishizaka, Yōjirō 1900-1986 (BFI, 2024)
A young man who's about to marry is torn between his fiancée and the love for his mother. His past, dreams and desires unfold simultaneously. [www.imdb.de]
Spielfilm. Japan. 1965
Bildformat: 2,35:1
Keywords: Film; Blu-Ray-Disc